FINANCIAL LITERACY AND PERFORMANCE OF MICRO, SMALL AND MEDIUM ENTERPRISES: A LITERATURE REVIEW - Imelfina Musthafa; Hefrizal Handra; Nasri Bachtiar; Werry Darta Taifur; Edi Ariyanto (Transpublika Publisher, 2023)
This research aims to examine various articles regarding the influence of financial literacy on the performance of MSMEs. The literature used in this research comes from indexed journal databases searching for the keywords